RELATIONSHIP BETWEEN SELF-TRUST AND ANXIETY AND LEARNING RESULTS : (Hubungan Antara Kepercayaan Diri dan Kecemasan Dengan Hasil Belajar) - Magfirah, Irma (Uniqbu Journal of Exact Sciences, 2021)
Students are not confident in themselves and always feel anxious in learning mathematics. This study aims to determine a picture of student confidence and anxiety with class XI SMA N 1 Buru's learning outcomes. The method used in this research is quantitative with an ex-post-facto approach. The results showed that data analysis results using descriptive statistics for self-confidence obtained an average value of 71.06 in the medium category; from 47 samples, the lowest score was 59, the highest value was 85, for anxiety, the average value was 72.00. medium type, from 47 samples, the lowest score was 52, the highest score was 87. And for learning outcomes, the average score was 68.94 in the medium category; from 47 samples, the lowest score was 60, the highest score was 85. As for the inferential statistical analysis results (Multiple Correlation) obtained Fcount> Ftable (8.92> 3.21), so H0 is rejected. By rejecting H0, H1 is accepted. Thus it can be concluded that there is a significant relationship between self-confidence and anxiety with student learning outcomes in mathematics class XI SMA Negeri 1 Buru.